Principals' Strategies for Advancing Education Through School Management - Mutniati, Vebri Putri; Burhanudin, Burhanudin; Hadi, Rizal; Yaltavera, Nabila; Latif, Muhammad Sabri (Jurnal Ilmiah Iqra', 2025)
This study explores the principal's efforts in enhancing the existence of MIN 2 Malang City through structured planning and effective school management. It focuses on four aspects: planning, organizing, implementing, and evaluating leadership practices. Using a descriptive qualitative approach and a case study method, data were collected through semi-structured interviews and documentation. The findings reveal that strong leadership, evident in resource management, teacher development, and extracurricular coordination, significantly improves the school's image and educational quality. This study offers strategic insights that can serve as a reference for other schools advancing education in Indonesia.